The Children's Classic Poetry Collection - Baxter, Nicola (Bookmart Limited, 1996)
An intricately illustrated anthology introduces children to a lifetime of pleasure in poetry and features a wide range of beloved poems by such writers as William Blake, Emily Brontë, Samuel Taylor Coleridge, Herman Melville, Edgar Allan Poe, Christina Rossetti, William Shakespeare and Robert Louis Stevenson. Includes a biographical section as well as an index of titles and first lines.
Keywords: General; Juvenile Nonfiction; Poetry